Integrated Disaster Management: Role Analysis of the Department of Disaster Prevention and Mitigation, Ministry of the Interior - Akkarapongpaiboon, Tossapon; Chirinang, Pensri; Raktham, Arun; Fuangchan, Somporn (Journal of Politics and Governance, 2021)
The objectives of this research are to 1) describe the integration of disaster management for relevant agencies under the coordination of the Department of Disaster Prevention and Mitigation, and 2) identify the technical methods for the integration of disaster management by the Department of Disaster Prevention and Mitigation. This research uses a qualitative research method. Data were collected by using in-depth interviews with key informants from relevant agencies, both government and civil, totaling 13 people. The data collection was analyzed for content analysis. The major findings revealed: 1) the Department of Disaster Prevention and Mitigation integrates disaster management with relevant agencies in three areas, including shared vision, strategy, and plan. There is no integration for disaster management with relevant agencies concerning shared practices, common resource database, and evaluation; 2) techniques for disaster management by the Department of Disaster Prevention and Mitigation include 2.1) enhancing knowledge and understanding about disaster-related issues to government agencies and civil organizations, 2.2) the promotion of knowledge to people and various agencies regarding culture, safety and participation in disaster management, 2.3) encouraging agencies to jointly organize disaster prevention and mitigation plans, 2.4) instilling attitudes and changing behavior in work, 2.5) creating a database of resources among agencies, and 2.6) allowing representatives from civil organizations to participate in the evaluation.